Quilombolas do Pará e mídias digitais: sociabilidade, conflito e mobilização online nas lutas por reconhecimento - Janine de Kássia Rocha Bargas (2018)
This research investigates the communicative practices of quilombos remnants communities in Pará. It investigates the relationship between appropriations of digital media, specifically the role of online interactions, in Facebook and Whatsapp, in their struggles over territorial rights, understood as parts of the struggles recognition. Based on the recognition theory of Axel Honneth and other social theorists, such as Mead, Simmel and Melluci, and in the dialogue with feminist theorists, such as Allen, Fraser, Crenshaw and Carneiro, I analyze the forms of appropriation of digital media and the online interactions of quilombolas, with the intention of observing, inside, how these aspects touch each other and where they differ. Thus, the following questions are examined: 1) what forms of sociability, conflict and mobilization are carried out by quilombolas, on Facebook and Whatsapp, in relation to the territory? 2) What are the similarities and differences between the occurrence of sociability, conflict and mobilization regarding the characteristics of each platform? 3) Under what circumstances do sociability, conflict, and mobilization intertwine or distance themselves in online interactions? How do sociability, conflict and mobilization on Facebook and Whatsapp contribute to or hamper the quilombolas' political actions about the territory? To develop the analysis, I performed a virtual ethnography and used complementary techniques, such as questionnaires and interviews. Part of the collaboration of this research resides in the joint analysis of categories considered relevant in the literature on social movements, however more commonly analyzed in a broad or separate way. Among the main results are: the mobility of the connection to the two media, whose main function is attributed by the quilombolas the exchange of information in a fast and updated way; the internal dynamics of the struggle, constituted intersubjectively, which revealed the existence of online social units and specific online territorialities; the strong interweaving of patterns of interaction related to sociability, conflict, and mobilization. In this sense, the imbrications between sociability, conflict and mobilization occurred in the online social units of the university quilombola students and the black quilombola women. These specificities make reference to the protagonism that both groups have claimed in the quilombola movement, either in their specific demands, or in broad guidelines, as those of the territory. In both digital media, therefore, online interactions are shaped as channels through which feelings, whether of belonging, of injustice or of engagement in struggles, are formulated, adjusted, readjusted and shared. In this way, other ways of political articulation can emerge as particularly important for quilombola struggles, either through internal adjustment, self-expression, visibility or the constitution of broader networks.